(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Currently, the study of concepts in language is one of the most promising areas of linguistics. The latest research into the connection between language and thinking makes it possible to consider concepts not only in philosophical, but also in linguistic, cultural and other aspects; A large number of their interpretations, classifications and research methods have been proposed. This article examines the concept of “nation” in English and Uzbek linguistic cultures